Chemotherapy Treatment of Elderly Patients (≥70 Years) with Non-Small Cell Lung Cancer: A Seven-Year Retrospective Study of Real-Life Clinical Practice at Karolinska University Hospital, Sweden. (14th July 2015) - Koyi, Hirsh; Hillerdal, Gunnar; Andersson, Olov; Kölbeck, Karl-Gustav; Liv, Per; Brandén, Eva
Abstract : An increasing proportion of cancer patients are aged >65 years and many are aged >70 years. Treatment of the elderly with lung cancer has, therefore, become an important issue; so we performed a retrospective study of our patients to demonstrate how elderly patients with NSCLC are treated in real-life, clinical practice. All patients aged ≥70 years with NSCLC at our department were reviewed retrospectively. In total, 1059 patients (50.8% of all NSCLC patients). Of these patients, 243 (22.9%) received chemotherapy, 164 (70.4%) of whom were treated with a platinum doublet using carboplatin. Second- and third-line chemotherapy were given to 31.4% and 13.9% of patients, respectively. Median overall survival was 289 and 320 days for male and female patients, respectively. Patients with performance status (PS) 0 experienced significantly better survival than patients with PS1 or PS 2: 410, 314, and 204 days, respectively. Age was of less importance, with patients aged 70–79 years versus those aged ≥80 years. Treatment of elderly NSCLC patients with chemotherapy is feasible if they have a good PS and appears to prolong survival. In this study, we found no significant differences in survival either between age groups or genders.